واقع ادارة العلاقات العامة في جامعة سوق اھراس دراسة تقیمیة من وجھة نظر الطلبة قسم العلوم الانسانیة - انمذجا - سلايمية نصيرة (My University, 2021)
Study summary Public relations plays an effective role in achieving its goals in university institutions, as it represents the face of the university that it overlooks on the external community, and is also considered a link between the university and its internal audiences, through which communication is carried out with various academic institutions and bodies at the local, Arab and international levels to convey the image of the university through the .means. different communication One of the most important audiences that public relations at the university should be concerned with is the public of students. Students’ attitudes are reflected in the general trends of citizens by virtue of their representation of all segments of society. On this basis, this study came to measure the effectiveness of communication activities practiced by public relations at the University of Muhammad Sharif, the assistantship of Souk Ahras, especially the Department of Science. Humanity as a model, where the :main question of the problematic of this study came as follows What is the level of students’ evaluation of the media and cultural - ?communication activities practiced by the communicators :Under this main question, the following sub-questions are included To what extent do communicators provide the required information and - ?the required sufficiency for students of the Humanities Department What are the most important means and methods used by communicators ?to communicate with students What are the students’ evaluation of the cultural and recreational - ?activities practiced by the communicators This study falls within the descriptive studies, to describe the practice of communicative activities performed by the administration of the .Department of Humanities at Muhammad Sharif University, assistantship In this study, we used the descriptive approach based on a comprehensive survey, and the study population was determined for all .humanities students We relied on the form as a basic tool in addition to observation to collect data, in addition to that, the student selected a representative sample of the study population by means of a stratified random sampling method to .obtain 122 items One of the most important results that we reached through this study is that the administration practices various communicative activities as the information received by the students is clear and of interest to them. It informs them of what is happening in the department and other colleges, but sometimes it does not arrive on time, and is relatively insufficient. These publications are published through various means of communication and by relying more on electronic communication, which has become the main focus in the communication process, which is what came in the theory of modern dialogue, which we relied on as a theoretical approach in our study through its orientation to the optimal use of new technologies to create interaction between the two sides of the process, which is also What Habermas called for is the “public virtual space.” To create a creative interactive space. The students also expressed their complete dissatisfaction, and the contentment was conservative due to the absence of the cultural and entertainment dimension that the administration practices in an occasional and not .always ------------------------------------- ملخص الدراسة تلعب العلاقات العامة دورًا فعالًا في تحقيق أهدافها في المؤسسات الجامعية، إذ تُمثل واجهة الجامعة التي تُطلّ عليها من المجتمع الخارجي، كما تُعتبر حلقة وصل بين الجامعة وجمهورها الداخلي، حيث يتم من خلالها التواصل مع مختلف المؤسسات والهيئات الأكاديمية على المستوى المحلي والعربي والدولي، لنقل صورة الجامعة عبر مختلف وسائل الاتصال. ومن أهمّ الفئات التي يجب أن تُعنى بها العلاقات العامة في الجامعة هو جمهور الطلاب، إذ تنعكس مواقفهم في الاتجاهات العامة للمواطنين بحكم تمثيلهم لجميع شرائح المجتمع. وعلى هذا الأساس، جاءت هذه الدراسة لقياس مدى فعالية الأنشطة الاتصالية التي تُمارسها العلاقات العامة في جامعة محمد الشريف، مساعدية سوق أهراس، وخاصةً قسم العلوم. الإنسانية نموذجًا، حيث جاء السؤال الرئيسي لإشكالية هذه الدراسة على النحو التالي: ما مستوى تقييم الطلاب للأنشطة الإعلامية والثقافية والتواصلية التي يمارسها القائمون على الاتصال؟ يندرج تحت هذا السؤال الرئيسي الأسئلة الفرعية التالية: إلى أي مدى يوفر القائمون على الاتصال المعلومات والكفاءة المطلوبة لطلاب قسم العلوم الإنسانية؟ ما أهم الوسائل والأساليب التي يستخدمها القائمون على الاتصال للتواصل مع الطلاب؟ ما تقييم الطلاب للأنشطة الثقافية والترفيهية التي يمارسها القائمون على الاتصال؟ تندرج هذه الدراسة ضمن الدراسات الوصفية، لوصف ممارسة الأنشطة التواصلية التي تمارسها إدارة قسم العلوم الإنسانية بجامعة محمد شريف، بمساعدتها. استخدمنا في هذه الدراسة المنهج الوصفي القائم على المسح الشامل، وتم تحديد مجتمع الدراسة من جميع طلاب العلوم الإنسانية. واعتمدنا على الاستمارة كأداة أساسية، بالإضافة إلى الملاحظة لجمع البيانات، وقد اختار الطالب عينة تمثيلية من مجتمع الدراسة، باستخدام أسلوب العينة العشوائية الطبقية، للحصول على 122 فقرة. ومن أهم النتائج التي توصلنا إليها من خلال هذه الدراسة أن الإدارة تمارس أنشطة تواصلية متنوعة، فالمعلومات التي يتلقاها الطلاب واضحة ومهمة لهم، وتُطلعهم على ما يحدث في القسم والكليات الأخرى، ولكنها أحيانًا لا تصل في الوقت المناسب، وتكون غير كافية نسبيًا. ويتم نشر هذه المنشورات عبر وسائل التواصل المختلفة، وبالاعتماد بشكل أكبر على التواصل الإلكتروني، الذي أصبح المحور الرئيسي في العملية التواصلية، وهو ما جاء في نظرية الحوار الحديث، والتي اعتمدنا عليها كمنهج نظري في دراستنا من خلال توجهها نحو الاستخدام الأمثل للتقنيات الحديثة لخلق تفاعل بين طرفي العملية، وهو ما دعا إليه هابرماس بـ"الفضاء الافتراضي العام". لخلق فضاء تفاعلي إبداعي. كما أعرب الطلاب عن استيائهم التام، وكان الرضا متحفظًا بسبب غياب البعد الثقافي والترفيهي الذي تمارسه الإدارة بشكل عرضي وليس دائمًا.
Keywords: ادارة العلاقات العامة، جامعة سوق اھراس